(untitled) (Research, Society and Development, 2021)
Sialolithiasis is a more common non-neoplastic disease that affects the salivary glands, attributed to the obstruction of salivary glands or their duct, by the formation of one or more stones. It is a disease that occurs more in larger salivary glands, with the submandibular one being the most affected. The etiology may be associated with the basic pH and the anatomy of the tortuous and ascending ducts. To describe the clinical case of an extensive sialolith in the submandibular gland and the diagnosis through clinical examinations with the aid of imaging tests. A female patient, attended the Oral Diagnosis Service of Stomatology Extension - SERPROBEM at Centro Universitário Cesmac for evaluation, complaining of a lesion in the left oral floor. Complementary imaging tests were requested: ultrasound, lateral teleradiography and conventional radiography (panoramic and occlusal), with the presence of a mineralized mass in the submandibular region. Surgical excision was performed, with preservation of the submandibular gland. With the association of clinical and imaging tests, it is easy to identify cases of sialolithiasis.